DEVELOPMENT AND VALIDATION HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR CHLOROGENIC ACID CONTENT DETERMINATION IN SIMPLICIAS AND GREEN COFFEE BEAN EXTRACT SUPPLEMENTS - Susanti, Lia
Obesity is a health problem that can increase the risk of cardiovascular disease, diabetes, and cancer. As a result of this, many slimming products are circulating in the market, one of which is green coffee beans, either in the form of green coffee bean simplicia (GCBS) or green coffee bean extract supplement (GCBE). Green coffee beans contain chlorogenic acid which is proven to have anti-obesity effect. Most of the existing analytical methods for analysis of chlorogenic acid, only focus on one form of sample, so a method that can be used to determine the level of chlorogenic acid in various sample forms is needed to guarantee the efficacy, safety, and quality of the product. Therefore, a high performance liquid chromatography (HPLC) analysis with UV detector was developed and validated in this research for determining chlorogenic acid in various sample forms. The results showed that the optimum conditions for HPLC were obtained with an Enduro C18G column, 150 mm x 4.5 mm x 5 ?m, isocratic elution mode with mixture of acetonitrile and 0.5% acetic acid (7.15:92.85 v/v) as a mobile phase, flow rate of 1.0 ml/minute, and UV detector at 327 nm. The validation results showed good specificity for the standard and both samples, with resolution between the chlorogenic acid and the adjacent peaks of around 2 – 3. The method also provided good linearity with a correlation coefficient (r)?0.999 and coefficient variation of linear regression function (Vx0)<2%, as well as limit of detection and quantitation are 0.42 ?g/mL and 1.38 ?g/mL respectively. This method also provided good level of accuracy with recoveries being 100.01 – 101.34% and 98.79 – 100.83% for GCBS and GCBE. Intraday and interday precision gave relative standard deviation (RSD)<2% and Horwitz Ratio (HorRat)<2. The results of the method validation indicate that the developed method has a good specificity, linearity, accuracy, and precision so that it can be used to determine the level of chlorogenic acid in simplicias and green coffee bean extract supplements.